The Source Value of Arabic Typikon-Manuscripts as Testimonials for the Byzantinization of the Melkites - Martin Lüstraeten (MDPI AG, 2021)
With the expansion of Islam, the patriarchates of Antioch, Jerusalem, and Alexandria were divided from the Byzantine Empire. The Orthodox Christians there still defined themselves as Byzantine Orthodox and began to adapt their liturgical customs by adopting Byzantine liturgical books. When Greek was not understood any longer, they began to translate and copy their liturgical books, thereby creating their own branch of tradition, which is marked by multilingualism, reception of their own Bible tradition as well as the exclusion of “neo-martyrs” from their calendar of saints.